2020
DOI: 10.3390/w12010252
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Stored Rainwater for Washing Purposes

Abstract: The use of rainwater for washing clothes is determined by its amount, composition and quality of washing. Raw rainwater is soft and free of pollution. The collected rainwater already contains pollution present in the atmosphere and washed away from roofs and other surfaces. It can also change its quality when stored in tanks. Washing clothes does not require drinking quality water but just clean, safe water that guarantees effective removal of dirt from fabrics. The study determined the physicochemical and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…This paper presents a general model for analysing residential RWH systems to assess the impact of rainfall patterns on the reliability of such systems in Poland. The recommended storage period for rainwater for individual RWH systems is 2-3 weeks, with the possibility of safe prolongation up to 4 weeks [46]. The analysis assumes a typical water storage period of 20 days, in which the rainwater tank capacity allows it to meet the indoor rainwater requirements.…”
Section: Rainwater Storage Period and Tank Capacitymentioning
confidence: 99%
“…This paper presents a general model for analysing residential RWH systems to assess the impact of rainfall patterns on the reliability of such systems in Poland. The recommended storage period for rainwater for individual RWH systems is 2-3 weeks, with the possibility of safe prolongation up to 4 weeks [46]. The analysis assumes a typical water storage period of 20 days, in which the rainwater tank capacity allows it to meet the indoor rainwater requirements.…”
Section: Rainwater Storage Period and Tank Capacitymentioning
confidence: 99%
“…Regarding washing dishes and bathing, 87.91% and 71.28% of households indicated that they use it to wash their dishes and bathing respectively. Regarding cleaning of house floor, 91.49% of respondent used it to clean the floor of the house (Struck-Sokolowska et al, 2020).…”
Section: Different Uses Of Rainwatermentioning
confidence: 99%
“…However, the quality of harvested rainwater will deteriorate through extreme events that occur from the worst climate change. The drought seasons will enhance the accumulation of pollutants on the roof including heavy metals from polluted air and the high capacity of accumulated water during flood events will promote mosquito breeding [95]. Under similar circumstances, the large storage system of PHS application will cause the rainwater quality to become worse due to the development of algae bloom and the reduction in dilution capacity (point sources) [96] during drought seasons as well as the rainwater that carries away harmful contaminations such as pesticides, oil and animal waste during the flash flooding.…”
Section: Water Qualitymentioning
confidence: 99%